Analisis Kepuasan Penghuni Terhadap Kualitas Bangunan dan Prasarana Perumahan Menggunakan Metode CSI dan IPA - Ayu Diah Nastiti; Fajar Dewantoro; Destiana Safitri (Institut Teknologi Garut, 2025)
The need for decent housing in Indonesia increases along with population growth, but the subsidized housing program still faces infrastructure problems that affect occupant satisfaction. This study analyzes the satisfaction of occupants of the Pane Residence 99 Housing using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. A descriptive quantitative approach was applied with a sample of 52 respondents through a Likert Scale questionnaire. The results showed a satisfaction index of 59.42% (quite satisfied). The IPA analysis revealed that 42.11% of attributes fell into Quadrant A (priority for improvement), such as drainage, clean water, health facilities, and roof-ceiling quality. As many as 10.53% of attributes fell into Quadrant B (maintain), such as road conditions and worship facilities. Recommendations include routine repairs to infrastructure and improving building quality. This study provides input for developers and the government to improve the effectiveness of the subsidized housing program.